Differential expression of galectin 3 in solid cell nests and C cells of human thyroid. Issue 2 (1st February 2003) - Faggiano, A; Talbot, M; Baudin, E; Bidart, J M; Schlumberger, M; Caillou, B
Abstract : Aims: To provide new insights into characterising solid cell nests and gain information that might help distinguish between solid cell nests and C cells. Methods: Thyroid tissue specimens from patients who had undergone prophylactic thyroidectomy for familial medullary thyroid cancer were immunostained for calcitonin, carcinoembryonic antigen, and galectin 3. Results: Solid cell nests displayed a strong and diffuse staining for carcinoembryonic antigen and galectin 3, but not for calcitonin. C cells located at the periphery of solid cell nests and in neighbouring follicles expressed both calcitonin and carcinoembryonic antigen but not galectin 3. These three markers were positive in medullary thyroid carcinoma. Conclusion: Galectin 3 immunoreactivity permits a better characterisation and differentiation between solid cell nests and C cells, avoiding the misidentification of two biologically and clinically different thyroid structures.